2022
DOI: 10.3390/medicina58030387
|View full text |Cite
|
Sign up to set email alerts
|

Oral Habits during the Lockdown from the SARS-CoV-2 Pandemic in the Romanian Population

Abstract: Background and Objectives: The SARS-CoV-2 pandemic led to changes in population daily patterns. In order to adapt oral health promotion measures for future similar conditions, the main objective of the study was to assess changes in dental hygiene and eating and smoking habits during the government lockdown in Romania. Materials and Methods: The cross-sectional study was conducted immediately after the end of the lockdown and consisted of 800 adult subjects. Data collection was done via an online survey. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Smoking cessation or reducing the frequency of smoking was noted in the present study, although only 11% of the participants were smokers before the pandemic. Similar findings were observed in recent studies on Italian and Romanian populations (Cărămidă et al, 2022;Di Renzo et al, 2020) where smoking was reduced among smokers who accounted for 25% and 30% of the total participants, respectively. On the other hand, more smoking was observed among Polish and British populations (Grogan et al, 2022;Sidor & Rzymski, 2020;Tzu-Hsuan Chen, 2020) which was related to increased stress and lack of physical activity during the lockdown.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Smoking cessation or reducing the frequency of smoking was noted in the present study, although only 11% of the participants were smokers before the pandemic. Similar findings were observed in recent studies on Italian and Romanian populations (Cărămidă et al, 2022;Di Renzo et al, 2020) where smoking was reduced among smokers who accounted for 25% and 30% of the total participants, respectively. On the other hand, more smoking was observed among Polish and British populations (Grogan et al, 2022;Sidor & Rzymski, 2020;Tzu-Hsuan Chen, 2020) which was related to increased stress and lack of physical activity during the lockdown.…”
Section: Discussionsupporting
confidence: 91%
“…This observation was in accordance with those in other studies (Caramida et al, 2022;Keles & Sancakli, 2020) where positive changes in lifestyle and oral home care routine during the pandemic were demonstrated. For example, in two of these studies (Cărămidă et al, 2022;Keles & Sancakli, 2020), the use of manual toothbrushes and dental flossing increased during the pandemic with those adopting such changes being more aware of the relationship between oral health and overall general health. In contrast, other studies (Brondani et al, 2021;Gotler et al, 2022) have shown negative behavior such as decreased timing and frequency of toothbrushing during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As the pandemic persisted, ensuring adherence to basic oral hygiene and maintaining appropriate oral health behaviors became increasingly arduous. It was observed that adherence to health-promoting behaviors such as regular brushing and exercising had a positive impact on health during the lockdown (29). Conversely, neglect of such routines correlated with detrimental effects on both general and oral health (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [ 17 , 25 ] have reported much lower percentages of patients who use floss, but there are also studies that have reported a percentage of up to 44% of patients who use it [ 26 ]. However, the general opinion is that dental floss used as an addition to interdental hygiene has not been sufficiently promoted in dental education [ 27 ]. However, tooth showers are unknown to all patients.…”
Section: Discussionmentioning
confidence: 99%